Measuring Students' Learning and Attitude as Exposed to Microscale Laboratory Experiments in Inorganic Chemistry - Roselle Urbano; Herbert De Jesus; Ponciano Dimla (International Journal of Education, Teaching, and Social Sciences, 2022)
Microscale chemistry is an approach to conducting chemistry experiments which can help overcome increased concerns about environmental pollution problems as well as rising laboratory costs. It is accomplished by using miniature labware and significantly reduced amounts of chemicals. The main goal of this study was to explore whether the use of microscale chemistry experiments can increase student’s understanding of chemistry concepts and improve attitude towards chemistry practical work. Quasi-experimental design without control group was used to determine from purposively selected class of 40 freshman students of Bachelor of Secondary Education (BSE). The students worked in groups on eight microscale chemistry experiments in a period of 8 weeks. Pre and post-test were administered before and after the treatment. Results revealed that microscale approach significantly improved student chemistry academic performance. Students’ perception of microscale is positive. Findings showed that the microscale approach can increase understanding of chemistry concepts. Keywords: learning, students’ attitude, microscale laboratory